Analisis Pengalaman Pengguna pada Website E-commerce Dengan Menggunakan Usability Testing dan User Experience Questionnaire (UEQ) (Studi pada Lazada.co.id, Blibli.com dan JD.id) - Ahmad Luthfi Teguh Adinegoro; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Rapid technological developments make the business began to process buying and selling online, this makes a lot of e-commerce began popping up in Indonesia which makes business competition was moved to online. Three e-commerce websites with high number of visitors in Indonesia is Lazada.co.id, Blibli.com and JD.id. This research aims to compare the three e-commerce websites that have the same characteristics and business processes in terms of usability and user experience, using the website media Lazada.co.id, Blibli.com and JD.id. In this research, there are 2 evaluation methods used, first objective evaluation by using direct test to the respondent in website usage using scenario task with parameter of task success rate, time per completed task, number of clicks during task completion and error during task performance, which was given to 10 respondents and UEQ Questionnaire which has 6 scales: attractiveness, efficiency, perspicuity, dependability, stimulation and novelty, given to 20 respondents. Respondents have different backgrounds with age range 16-65 years old who have never used the three websites tested. Second, subjective evaluation using focus group discussion for getting more detailed user perception and problem. From both tests performed it can be concluded that the website Blibli.com is superior to Lazada.co.id and JD.id.